Computational Design of Electrocatalysts for Hydrogen Evolution Reaction – From Electronic Structure to Nanometer Scale - Pašti, Igor A. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Hydrogen evolution reaction (HER) is one of the most important electrocatalytic reactions, considering both practical and theoretical aspects. Long time ago an idea had appeared to link the physical properties of the electrocatalyst with its HER performance. This idea has evolved over the years and now we have some quite well defined catalytic activity descriptors which can be used to both explain and predict activity. Computational methods have been proven as extremely valuable in describing physical and chemical properties of solid surface, allowing for rather accurate predictions of novel materials with enhanced HER activities. In this contribution we shall address the main aspects of the computational design of HER electrocatalysts, starting from the concept of the catalytic activity descriptor and the electronic structure level to nanometer domains. Such level of description requires multiscale approach to address phenomena at different temporal and spatial domains. In specific, the attention will be paid to novel thin layer HER catalysts and the formation of supported HER catalysts where boundary phenomena play extremely important role in enhancing HER activity.